Answer:
Explanation:
Multiply both sides of the equation by e
d*e - 7*e = 4d + 3
de - 7e goes into the first box on top.
==================
The second box is obtained in two steps.
Step One
Add 7e to both sides.
de - 7e + 7e = 4d + 3 + 7e
de = 4d + 3 + 7e
Step Two
Subtract 4d from both sides.
de - 4d = 4d - 4d + 3 + 7e
de - 4d = 3 + 7e
de - 4d goes into the middle box.
================================
Take out d as a common factor
d(e - 4) = 3 + 7e
d(e - 4) goes into the third box from the top.
=============================
Divide both sides by e - 4
3 + 7e
d = ---------
e - 4